Criterion of Criticism in Classical Arabic Poetry: The Concept of Amūd al-shi'r in Abū Alī al-Marzūqī - Hatice Derebaşı; Şükran Fazlıoğlu (Şarkiyat Mecmuası)
The concept of amūd al-shi‘r, denoting the fundamental aspects of poetry within Arabic literary criticism, serves as the cornerstone and foundation representing the classical Arabic poetry method and style in poetic composition. Literary critics have endeavored to establish qualifications, principles, and criteria for the art of poetry under the umbrella of amūd al-shi‘r, seeking to discern between good and subpar poetry, ancient and contemporary works, and facilitating comparisons between poems. This concept has been addressed in diverse manners by Arab critics and literary scholars over time, culminating in its definitive form with the language and literature scholar Abū Alī al-Marzūqī (d. 421/1030) from Isfahan. This study aims to explore the equivalent of the amūd al-shi‘r concept, rooted in classical Arabic poetry, as articulated by Abū Alī al-Marzūqī. It seeks to determine the boundaries and criteria of this concept and ascertain its significance in the domain of literary criticism. To this end, the emergence and evolution of the term will be briefly outlined, focusing on the contributions of critics who paved the way for Marzūqī and laid the groundwork for the theory, which Marzūqī further shaped and systematized. Subsequently, an investigation will be conducted into the extent to which the author expanded upon previous works, the areas in which he concurred or diverged from prior authors, and the influence of his ideas on subsequent literary thought.